2009
DOI: 10.1021/ja902794w
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Group III Biheterocyclic Complexes

Abstract: Group III alkyl complexes supported by a ferrocene diamide ligand (1,1'-fc(NSi(t)BuMe(2))(2)) have been found to be reactive toward aromatic N-heterocycles such as 1-methylimidazole and pyridines. These reactions were investigated experimentally and computationally. An initial C-H activation event is followed by a coupling reaction to form biheterocyclic complexes, in which one of the rings is dearomatized. In the case of 1-methylimidazole, the biheterocyclic compound could not be isolated and further led to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
93
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(95 citation statements)
references
References 57 publications
2
93
0
Order By: Relevance
“…The reaction of 6 mbi with quinoline was investigated in order to determine whether this substrate undergoes CeH activation, as observed with a scandium benzyl supported by the same ferrocene-diamide ligand [22], or alkyl transfer, as observed with isoquinoline and group 3 metal benzyl complexes [23]. Consequently, when 6 mbi was mixed with quinoline in hexanes, at room temperature, no toluene formation was observed after 15 h, ruling our CeH activation (Eq (2)).…”
Section: (1)mentioning
confidence: 99%
“…The reaction of 6 mbi with quinoline was investigated in order to determine whether this substrate undergoes CeH activation, as observed with a scandium benzyl supported by the same ferrocene-diamide ligand [22], or alkyl transfer, as observed with isoquinoline and group 3 metal benzyl complexes [23]. Consequently, when 6 mbi was mixed with quinoline in hexanes, at room temperature, no toluene formation was observed after 15 h, ruling our CeH activation (Eq (2)).…”
Section: (1)mentioning
confidence: 99%
“…[14][15][16] Our group has studied extensively the reactivity of group 3 metals and uranium alkyl complexes supported by diamide ligands towards heterocyclic aromatic compounds. [17][18] Benzyl complexes were found to ring open 1-methylimidazoles, [19][20][21][22][23] effect C-C coupling of pyridines, [24][25] and alkyl transfer to isoquinoline. [26][27] In those cases, the ligand framework was a ferrocenediamide that could support a weak donor-acceptor interaction between the metal in the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…This observation highlights the difference in the reactivity of the uranium complexes from that reported earlier for scandium complexes: [14,15] the scandium imidazolyl complex analogous to 2 mi cannot be generated in the absence of a base; therefore, a stronger Lewis base than 1-methylimidazole would be required to displace this ligand. Thermal-ellipsoid representation of 3 A (left, 50 % probability) and 3 B (right, 35 % probability); H atoms, solvent atoms, tBu methyl groups, and disordered counterparts were removed for clarity.…”
mentioning
confidence: 61%
“…[10] Our interest in the reactions of electrophilic alkyl complexes [11,12] supported by a ferrocene (fc) diamide ligand with aromatic N heterocycles [13][14][15] prompted us to investigate the reactivity of the uranium dibenzyl complex 1-(CH 2 Ph) 2 ((NN fc )U(CH 2 Ph) 2 ; NN fc = 1,1'-fc(NSitBuMe 2 ) 2 ) [11,16] with imidazoles. It has been reported that actinide complexes are more reactive than analogous Group IV complexes towards aromatic N heterocycles, and that C À H activation occurs from neutral dialkyl complexes as opposed to the cationic alkyl complexes of group IV metals.…”
mentioning
confidence: 99%
See 1 more Smart Citation